1995
DOI: 10.1093/ije/24.4.821
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Hepatitis A among Irish Haemophiliacs

Abstract: Although person-to-person transmission is likely to have caused a few of the cases, the results of our investigation suggest that the major contributing factor was exposure to certain batches of SD-treated factor VIII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…Although a rare occurrence, transmission through the parenteral route is possible, with cases reported after blood transfusions in neonates and adults [3][4][5]. Recently, cases of hepatitis A have been linked to receipt of factor VIII concentrates in Europe [6][7][8][9] and South Africa [10] and to receipt of factor VIII and IX concentrates in the United States [11].…”
Section: The Duration Of Viremia and Time Course For Development Of Imentioning
confidence: 99%
“…Although a rare occurrence, transmission through the parenteral route is possible, with cases reported after blood transfusions in neonates and adults [3][4][5]. Recently, cases of hepatitis A have been linked to receipt of factor VIII concentrates in Europe [6][7][8][9] and South Africa [10] and to receipt of factor VIII and IX concentrates in the United States [11].…”
Section: The Duration Of Viremia and Time Course For Development Of Imentioning
confidence: 99%
“…In Ireland, the HAV infection cluster was confined to the haemophilia A patients treated with sol vent-detergent-treated factor VIII produced by Octapharma (Vienna) [3], These findings indicate that factor IX concentrates can transmit HAV This is supported by a recent report [16] of a case of HAV transmission by solvent-detergent-treated fac tor IX concentrate, full details of which are not yet available. It is possible that previous clusters of HAV infection associ ated with such blood products may not have been noticed due to the widespread belief that factor concentrates did not transmit HAV infection.…”
Section: Resultsmentioning
confidence: 87%
“…A limited retrospective review of the infectivity of this batch has been undertaken from data obtained in 1991-1992 during investigation of the hepatitis A cluster in the hae mophilia A cases [3]. This showed that of the 21 patients who either definitely (n = 8) or probably (n = 13) received batch 90742 all were anti-HAV IgG positive in 1991-1992.…”
Section: Manufacture Of Factor IX Concentratementioning
confidence: 99%
See 1 more Smart Citation
“…The patients receiving clotting factor concentrate, particularly products inactivated by solvent-detergent which was ineffective against nonlipid enveloped viruses such as HAV (25)(26)(27)(28)(29)(30). In developed countries, hepatitis A vaccine is recommended for HAV seronegative people with clotting disorders, and those with CLD (31,32).…”
Section: Discussionmentioning
confidence: 99%